An Approach of Machine Learning to Get the Popularity Vaticinator of Vehicle (International Journal of Innovative Research in Engineering & Management, 2022)
Today could be a world of technology  with a predicted way forward for a machine reacting and  thinking same as human. during this method of rising  computing, Machine Learning, information Engineering,  Deep Learning plays an important role. during this paper,  drawback the matter} is known as regression or  classification downside and here we've resolved a true  world problem of recognition vaticinator of a auto  company persecution machine learning approaches.
Keywords: Machine Learning; Regression; Classification; Supervised Machine Learning; Logistic Regression; KNN; Random Forest